Banks' search for yield in the low interest rate environment: A tale of regulatory adaptation - J. Christina Wang (Federal Reserve Bank of Boston, 2017)
This paper examines whether the low interest rate environment that has prevailed since the Great Recession has compelled banks to reach for yield. It is important to recognize that banks can take on a variety of risks that offer higher yields today but incur different forms of future losses. Some losses, such as mark-to-market losses due to yield increases, can be avoided with accounting treatments whereas others, chiefly credit losses, cannot. A simple model shows that a bank's incentive to take on risks for which potential future losses can be managed, such as interest rate risk, is countercyclical, especially if a bank is capital constrained. This study thus focuses on a bank's exposure to interest rate risk through a maturity mismatch between its assets and liabilities. It finds evidence that the banks that faced less enhanced regulation after the financial crisis, especially those institutions used to having a higher net interest margin before the crisis, took on assets with longer maturities or prepayment risk, even while their source of funding shifted toward more transaction and saving deposits as a result of the near zero short-term interest rates. In contrast, those banks designated as systematically important and thus subjected to expanded post-crisis regulations have substantially shortened the average maturity of their assets since the crisis. There is some evidence that greater maturity mismatch is slightly more associated with a higher net interest margin during the post-crisis years. After the taper tantrum in 2013, these two groups of banks also adjusted their securities holdings in different ways, consistent with the differential regulatory accounting treatment.
Keywords: G11; G18; G21; E41; E52; 330; banks; reaching for yield; maturity mismatch; regulation; zero lower bound